Flying high : women on wings gives lift to women in rural India - Comiteau, Lauren; Yue, Tao, active 2020 (London : Rotterdam School of Management, Erasmus University, 2020)
Women on Wings, a non-profit NGO, created employment for women in rural India by using its network of financial experts to advise existing social enterprises on how to grow their businesses. Founded in 2007, its goal was to create one million jobs in 10 years. Co-founder Maria van der Heijden’s premise behind the project was, "If you invest in women, you invest in the family. And that means society. If a woman has her own income, she spends it on the children, on education and food. With a job and an income, the whole family rises up." The aims of emancipation and development were embedded in the organisation’s operations and strategy. The problem was that time was running out. There were only nine years left to fulfil the SDG goals. The Covid-19 crisis only added to the pressure.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Social entrepreneurship -- India -- Case studies; Rural women -- India -- Case studies